1990
DOI: 10.1182/blood.v75.7.1455.1455
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of factor XIIIa in a canine model of coronary thrombosis: effect on reperfusion and acute reocclusion after recombinant tissue- type plasminogen activator

Abstract: The effect of inhibition of factor XIIIa with 2-(l-acetonylthio)-5- methylthiazolo[2,3-b]1,3,4-thiadiazo lium perchlorate (L-722,151) on coronary thrombolysis and reocclusion was studied in an acute dog model of electrically induced coronary thrombosis. L-722,151 (0.1 mg/kg/min intravenously [IV] or placebo was administered 15 minutes before current initiation (150 microA) and for the duration of the experiment (270 minutes). Fifteen minutes after thrombus formation, heparin (300 U/kg, IV) was administered, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 22 publications
2
31
0
3
Order By: Relevance
“…Previous studies in rabbits and dogs showed that pharmacologic FXIII inhibition accelerates thrombolysis in response to administration of therapeutic lytic agents, suggesting that prophylactic FXIII inhibition may facilitate thrombus dissolution. Notably, however, in both the pharmacologic and now genetically engineered animal models, FXIII reduction failed to alter the events leading to the formation of occlusive thrombi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in rabbits and dogs showed that pharmacologic FXIII inhibition accelerates thrombolysis in response to administration of therapeutic lytic agents, suggesting that prophylactic FXIII inhibition may facilitate thrombus dissolution. Notably, however, in both the pharmacologic and now genetically engineered animal models, FXIII reduction failed to alter the events leading to the formation of occlusive thrombi.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in rabbits and dogs showed that pharmacologic FXIII inhibition accelerates thrombolysis in response to administration of therapeutic lytic agents, suggesting that prophylactic FXIII inhibition may facilitate thrombus dissolution. Notably, however, in both the pharmacologic and now genetically engineered animal models, FXIII reduction failed to alter the events leading to the formation of occlusive thrombi. Collectively, these data from multiple, independent experimental models of arterial thrombosis suggest FXIIIa does not contribute prominently to the molecular events that promote artery occlusion, and that inhibiting FXIIIa, alone, would not prevent the initial formation of arterial thrombi or associated tissue ischemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…101 Similarly, in a canine model of coronary artery thrombosis, FXIIIa inhibition accelerated reperfusion and reduced residual thrombus mass following tPA administration. 102 Notably, in both models, this effect was limited to animals pretreated with the FXIIIa inhibitor, and was not observed in animals infused with FXIIIa inhibitor after thrombus induction. 101,102 This finding suggests that FXIII activation and cross-linking activity occur early during thrombogenesis.…”
Section: Contribution Of Fxiii To Arterial Thrombosismentioning
confidence: 96%
“…102 Notably, in both models, this effect was limited to animals pretreated with the FXIIIa inhibitor, and was not observed in animals infused with FXIIIa inhibitor after thrombus induction. 101,102 This finding suggests that FXIII activation and cross-linking activity occur early during thrombogenesis. Accordingly, using a fluorescent peptide derived from α 2 -antiplasmin to probe for FXIIIa activity in mice, Jaffer et al 103 detected signal enhancement within 30 minutes of thrombus induction, indicating early generation of FXIIIa activity during thrombogenesis.…”
Section: Contribution Of Fxiii To Arterial Thrombosismentioning
confidence: 96%